The adaptation and feasibility of dialectical behaviour therapy for adults with intellectual developmental disabilities and transdiagnoses: A pilot community‐based randomized controlled trial. Issue 3 (17th February 2021) - Jones, Jessica; Blinkhorn, Ashleigh; McQueen, Meg; Hewett, Laura; Mills‐Rogers, Mary‐Jane; Hall, Layla; Althagafi, Lujain; Hudson, Chloe; Gierc, Madelaine; Wright, Kristyn; Goettl, Hannah; Keogh‐Lim, Daniel; et al.
Abstract: Introduction: Preliminary evidence suggests dialectical behaviour therapy (DBT) may be beneficial for persons with intellectual disabilities. This pilot randomized controlled trial aimed to determine the feasibility of adapted DBT for adults with intellectual disabilities and co‐morbid psychiatric disorders in the community. Methods: An adapted DBT programme (aDBT‐ID) was delivered to adults with mild‐to‐moderate intellectual disability ( n = 20) and their caregivers ( n = 20). A single‐blind, mixed‐methods design was employed with treatment ( n = 10) and control ( n = 10). In addition to feasibility, pre–post‐measures of emotional regulation, anger and mental health were taken from clients and caregivers. Results: Results suggest it was feasible and beneficial to deliver adapted DBT in the community. Qualitative findings found both participants and caregivers were satisfied with the treatment delivery. No differences between conditions were found. Conclusion: This pilot study highlights the feasibility of adapted DBT for individuals with intellectual disabilities and the practicalities of delivering community‐based inclusive research.